Studi Kromatografi Lapis Tipis Preparatif pada Pelat Silika dan Kromatografi Cairan Kinerja Tinggi pad a Kolom C18 dari Senyawa-Senyawa Hasil Biokonversi Solasodine - J. Kantasubrata; T. Y. Fitri; V. A. Halomoan; Buchori Buchori; A. T.Karossi (Jurnal Kimia Terapan Indonesia, 1994)
The separation of solasodine bioconversion products-after fermentation with Mycobacterium phlei DSM 43286 has been carried out, using preparative thin layer chromatography on silica plate with chloroform-ethanol (48:1) mixture as an eluent. Chromatographic cross check of the compound being separated has also been done. In addition to the silica stationary phase, the separation of bioconversion products using CIS has also been explored. Solanesol and six derivatives of androstane or androstene standards could be well separated on Ci8 plate using methanol-chloroform (4:1). For the High Performance Liquid Chromatography (HPLC) separation on C18 column, the mixture of methanol-water was used instead of methanol-chloroform, since with the latter eluent, compounds being separated were eluted together with the solvent peak. The optimum resolution of solasodine bioconversion products could only be attained when the gradient elution technique using the mixture of methanolwater was used.